Análisis de la Sostenibilidad del Sistema Agropecuario de la comunidad de San Ignacio, Parroquia Toacaso, cantón Latacunga, Provincia de Cotopaxi periodo 2018-2019. - Iza Anguisaca, Vilma Leonela (2019)
The present investigation was carried out in the community of San Ignacio,Toacaso Parish. The community of San Ignacio, is composed of small and medium producers whose main economic source is livestock and, to a lesser extent, agriculture. The objective of this research is to evaluate the sustainability of the agricultural system of the community of San Ignacio, Toacaso Parish, Cantón Latacunga, Cotopaxi Province using the MESMIS methodological framework. In the present investigation, three main axes were worked (social, economic and environmental) for which the Framework for the Evaluation of Natural Resources Management Systems was used with Indicators of Sustainability (MESMIS). Regarding the procedure carried out, it was the analysis of the agricultural systems of the community where 19 sustainability indicators were selected and 22 farms of the community were evaluated. It was possible to observe the different changes that occurred during the period 2015-2019, thus, in 2019 there was greater sustainability in the agricultural and socioeconomic systems, the most sustainable parameters within the farms of the San Ignacio community were the crops produced by the farm, the diversity of crops with different functions, the dairy production per farm, livestock feed, animal diversity, seed diversity, recklessness, independence and satisfaction since at the time of executing the project different activities were carried out (training , technical assistance), on the other hand it was observed that should be put more emphasis is on the incorporation of organic matter, the proper use of fertilize and control of pests and diseases as they are the most unsustainable since at the time of the different activities focused more on the part of livestock being the main source of income for families.